Urazy głowy u dzieci - aktualne algorytmy diagnostyczno-lecznicze - Urban, Paulina; Chądzyński, Piotr; Saramak, Kamila; Jóźwiak, Sergiusz (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Head injuries in children are a common cause of consultation in emergency department. Glasgow Coma Scale (GSC) and, in case of infants, modified Glasgow Coma Scale are widely used for the evaluation of symptoms severity and divide head trauma into mild, moderate and severe. Guidelines concerning preliminary approach to mild head injury are based on the risk factors of intracranial injury. Risk of injury assessment criteria proposed by Polish Association of Paediatric Surgeons indicate the best places of medical consultation. Several guidelines concerning utility of head computed tomography (PECARN - Paediatric Emergency Care Applied Research Network, CHALICE - Children's Head Injury Algorithm for the Prediction of Important Clinical Events, CATCH - Canadian Assessment of Tomography for Childhood Head Injury) as well as time of patient observation and repetition of computed tomography scan were proposed. Special attention should be directed towards young athletes; in their case Child SCAT3 (Sport Concussion Assessment Tool 3) and SCAT3 are recommended. The goal of medical care of children with severe head trauma is mainly to eliminate secondary injury. Patients often require intensive monitoring and treatment of hypoxia, hypotension, hyperthermia and increased intracranial pressure. The clinicians should bear in mind the co-occurrence of spine trauma and post-traumatic seizures. Presented guidelines not only could influence patient care, but also decrease medical expenses.